EZH2 Mediates miR-146a-5p/HIF-1α to Alleviate Inflammation and Glycolysis after Acute Spinal Cord Injury. (20th May 2021) - Ni, Shuangfei; Yang, Bo; Xia, Lei; Zhang, Huafeng
Abstract : Acute spinal cord injury (ASCI) is a severe traumatic disease of the central nervous system, the underlying mechanism of which is unclear. This study was intended to study the role of EZH2 and miR-146a-5p/HIF-1 α in inflammation and glycolysis after ASCI, providing reference and basis for the clinical treatment and prognosis of ASCI injury. We used lipopolysaccharide (LPS) to induce inflammation of microglia, and we constructed the ASCI animal model. qRT-PCR detected the relative expression levels of EZH2, HIF-1 α, miR-146a-5p, IL-6, TNF- α, IL-17, PKM2, GLUT1, and HK2 in cells and tissues. Western blot was performed to detect the expression levels of EZH2, HIF-1 α, H3K27me3, IL-6, TNF- α, IL-17, PKM2, GLUT1, and HK2. ChIP verified the enrichment of H3K27me3 in the miR-146a-5p promoter region. Bioinformatics predicted the binding sites of HIF-1 α and miR-146a-5p, and dual-luciferase reporter assay verified the binding of HIF-1 α and miR-146a-5p. ELISA detects the levels of inflammatory factors IL-6, TNF- α, and IL-17 in the cerebrospinal fluid of rats. The GC-TOFMS was used to detect the changes of glycolytic metabolites in the cerebrospinal fluid of rats. EZH2 could mediate inflammation and glycolysis of microglia. EZH2 regulates inflammation and glycolysis through HIF-1 α . EZH2 indirectly regulated the HIF-1 α expression by mediating miR-146a-5p. EZH2 mediates miR-146a-5p/HIF-1 α to alleviate inflammation and glycolysis in ASCI rats. In the present study, our results demonstrated that EZH2 could mediate miR-146a-5p/HIF-1 α to alleviate the inflammation and glycolysis after ASCI. Therefore, EZH2/miR-146a-5p/HIF-1 α might be a novel potential target for treating ASCI.